Language Environments and Spoken Language Development of Children With Hearing Loss. (17th July 2020) - Arora, Sonia; Smolen, Elaine R; Wang, Ye; Hartman, Maria; Howerton-Fox, Amanda; Rufsvold, Ronda
Abstract: This study examined the relationships between adult language input and child language production in regard to the quantity and diversity of spoken language, as well as children's knowledge of basic concepts and vocabulary. The quantity and diversity of language provided by teachers and parents were related to children's language output and knowledge. Language ENvironment Analysis technology audio-recorded the language environments of 26 preschool children with hearing loss over 2 days. The language samples were analyzed for quantity (adult word count, child vocalization count, and conversational turn count) and diversity (lexical diversity, syntactical complexity, and clausal complexity) of language. Results indicated a relationship between adult language input and child language production, but only in regard to the quantity of language. Significant differences between the teachers and parents were reported in regard to the diversity of adult language input. These results suggest that the language input provided by adults across environments (school versus home) is considerably different and warrants further investigation.